Improving the students' ability in writing descriptive texts through collaborative writing technique - Supiani Supiani (Journal on English as a Foreign Language, 2015)
The main objectives of the study to improve the students’ ability in writing descriptive texts and know the strengths and weaknesses of the implementation of collaborative writing technique in improving students’ writing ability of descriptive texts. The Classroom Action Research was employed in this study. The subject of the study was 28 of eighth grade students of the SMP Negeri 1 Pelaihari in the Academic Year of 2011/2012. This action research was conducted in two cycles. Each consisted of planning, implementing, observing, and reflecting the action. In collecting the data, the data are obtained from the questionnaire, interview, and observation and also from the writing tests. The result of this study shows that collaborative writing technique can improve the students’ ability in writing descriptive texts. This is proved by the significant increase of the mean score of the post-test cycle 1 and post-test cycle 2. Besides, the students have become more motivated to study English especially in writing.